2020
DOI: 10.1002/oby.22828
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Consistency of Self‐Weighing to Promote Weight‐Loss Maintenance

Abstract: This study aimed to investigate the roles of frequency and consistency of self-weighing in promoting weight-loss maintenance. Methods: Participants were 74 adults who completed a 3-month internet-based weight-loss program followed by a 9-month nointervention maintenance period. Frequency of self-weighing was defined as the number of days that participants self-weighed during the maintenance period via a study-provided smart scale. Consistency was defined as the number of weeks that participants self-weighed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Other factors, such as long-term goals, motivation for self-weighing, and behavioral factors as well as diet and physical activity, may have stronger effects on weight loss efforts, although weight-loss–promoting practices are important. It has also been suggested that the consistency of self-weighing is more important than the frequency of self-weighing [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other factors, such as long-term goals, motivation for self-weighing, and behavioral factors as well as diet and physical activity, may have stronger effects on weight loss efforts, although weight-loss–promoting practices are important. It has also been suggested that the consistency of self-weighing is more important than the frequency of self-weighing [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The second aim was to examine whether changes in weighing variables (i.e., self-weighing, reaction to weekly weighing, sensitivity to weight gain and shape/weight acceptance) following treatment were associated with treatment outcomes among those with and without food addiction following BWL treatment. Prior work examining self-weighing within adult samples with overweight highlight the significant benefits of consistent self-weighing on weight loss outcomes [ 18 , 19 , 20 , 21 ], yet individuals with binge-eating or those with a history of eating disorders are often excluded from weight-loss studies. The present findings suggest that frequency of weighing was not significantly related to adverse treatment outcomes, including binge-eating, percent weight loss and eating-disorder psychopathology in a clinical sample of individuals with obesity and BED.…”
Section: Discussionmentioning
confidence: 99%
“…We are unaware of any studies that have prospectively examined changes in behaviors among individuals with and without food addiction during and after treatment. One key component of BWL includes self-monitoring of weight during treatment, and prior work suggests that more frequent or consistent self-weighing is associated with improved weight-loss outcomes [ 18 , 19 , 20 , 21 ]. Several prospective studies examining adults during weight-loss treatment found that greater frequency of self-weighing was not associated with adverse psychological outcomes such as binge-eating [ 22 ], depression [ 20 , 21 , 23 ] or other forms of disordered eating, such as compensatory strategies [ 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, several studies report a greater weight loss in patients using smart scales than in patients self-reporting weight loss or being weighted only during visits [11,12]. Last, data exist on the importance of weight variability in final weight loss and weight maintenance [13][14][15]; using smart scales at home with automated data treatment could help health care professionals and patients in achieving and maintaining greater weight loss [16].…”
Section: Interest For Follow-upmentioning
confidence: 99%